(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2024)
Diclipterarox burghiana Nees. is a shrub which belongs to the family Acanthaceae. The present study was under taken in view of the medicinal importance of this genus and the lack of any report on its essential oil composition and antibacterial activity. Essential oil from whole aerial part, including flowers, of the plant was extracted by steam distillation method and analyzed by GC-FID and GC-MS.In all, sixty-nine compounds constituting 85.5% of the total oil composition have been identified. The essential oil contained high concentrations of non-terpenic compounds (33.5%), while the terpenoid compounds had a higher concentration still (52.0%). The unidentified portion contained several minor constituents with ambiguous Mass Spectra. The major constituents of the essential oil were identified as β-panasinsene (11.2%), phytol (10.0%), pentadecanal (8.6%), cis, cis, cis-7,10,13-hexadecatrienal (7.6%), linalool (4.2%) and cameroonan-7-α-ol (4.2%).The antioxidant activity of four different extracts (whole aerial parts) was performed by two methods namely,DPPH assay and metal chelating assay. Significant results were obtained in each case at 100µg/mL concentration. For antibacterial screening, the essential oil exhibited highest activity against Gram-negative Pasteurella multocida (15.66 ± 0.57mm) and Gram-positive Bacillus subtilis (13.00 ± 1.00mm). The highest activity ofethyl acetate extract was recorded against Gram-negative Pasteurella multocida (12.00 ± 0.00mm).The hexane extract of the plant was found most active against Gram-positive Enterococcus faecalis (13.33 ± 0.57mm). The chloroform extract showed highest activity against Gram-negative Xanthomonas phaseoli (16.33 ± 1.15mm) and Gram-positive Enterococcus faecalis (12.00 ± 1.00mm). For methanol extract, highest activity was observed against Gram-negative Agrobacterium tumefaciens (10.66 ± 0.57mm) and Gram-positive Enterococcus faecalis (10.33 ± 0.57mm). The essential oil exhibited highest antifungal activity against the fungal strains namely, Aspergillus niger(17.66 ± 0.57mm) followed by Aspergillus flavus (16.66 ± 0.57 and Candida albicans (16.33 ± 0.57mm).The essential oil and extracts from this plant species may be utilised to control various microbial infectious diseases and may also serve as an antioxidant supplement.